Study on the stability of fractional order Ebola virus model. (2018) - Wei, Changcheng; Fang, Juanyan
This paper attempts to study the dynamical behaviour of the fractionalorder model of Ebola virus. Based on the basic reproduction number, the stability of this model's equilibrium points is analysed.